The use of mint and thyme extracts as eco–friendly natural dyes and the antimicrobial properties of dyed products (Kuwait Journal of Science)
In this study, the dyestuff and antimicrobial properties were examined using extracts obtained from mint (Mentha spicata L.) and thyme (Thymus vulgaris L.) plants. Cotton and woolen fabric samples were used in the dyeing process using pre–, meta–, post– mordant, and non–mordant dyeing methods. CuSO4, FeSO4, and AlK(SO4)2 mordants were used as stabilizers and color changers. The color analysis of the dyed textile samples was evaluated in terms of rubbing, washing, and light fastness values. The color codes were determined with the Pantone Color Guide, and the L∗, a∗, b∗, C∗, ho, and K/S values were detected with a color measurement spectrophotometer. The highest K/S value was measured as 23.050 for FeSO4 with meta–mordanting method for dyed wool yarn using thyme extract. The antimicrobial properties of the dyed fabrics were determined by the disk diffusion method. Among the mordants used, dyeing with CuSO4 showed better antimicrobial properties than other mordants. As the textile dyed products possess antimicrobial properties, we believe their use in health centers will make a positive contribution to hygiene. As a result, it was determined that extracts obtained from mint (Mentha spicata L.) and thyme (Thymus vulgaris L.) plants were effective natural dye sources for textile products. © 2024 The Authors